Brewing microbiology – Lactic Acid Bacteria and Cultivation Methods of Their Detection – Part III - Petra Kubizniaková; Eva Vontrobová; Tomáš Vrzal; Dagmar Matoulková (Kvasný průmysl, 2017)
Here we present data on the growth of 10 strains of Lactobacillus and Pediococcus species on solidifi ed culture media, e.g. MRS agar and its various modifi cations, the media Raka-Ray, NBB, UBA, etc. The rate of formation of bacterial colonies and their size were monitored. Strains were inoculated into culture media directly from beer, in two varieties – with previous gradual adaptation to beer and without the adaptation phase. Some strains showed increased long-term survival ability in beer if the bacteria were gradually transferred to a medium with increasing concentration of beer (adaptation phase). In subsequent testing of cultivation media, MRS and its modification were evaluated as the most effective. Raka-Ray was evaluated as the least suitable for the detection of lactic acid bacteria.